Understanding effective professional employee management from the perspective of McGregor's theory of X and Y - Wang, Yiran; Wider, Walton; Chan, Choon Kit; Maidin, Siti Sarah; Mustafa, Nurul Aliah (International Journal of Management and Sustainability, 2023)
The purpose of this study is to investigate the relationship between key drivers of effective management of professional employees in Malaysian universities. We adapt McGregor's Theory of X and Y to identify three key drivers: employee feedback, reward, and work freedom. Utilizing a cross-sectional design, the research instruments for this study were derived from prior studies. A total of 156 online questionnaires were collected from professional employees working at Malaysian universities. We tested the research hypotheses using SPSS Version 26.0. The findings of the analysis demonstrate that each of the primary factors, namely employee feedback, reward, and work freedom, exhibits a statistically significant and positive influence on the attainment of effective management. This study demonstrates that effective management, which directly affects the professionalism of university employees, is significantly influenced by employee feedback, reward, and work freedom. The study's findings have crucial implications for policymakers and other stakeholders in the education sector. The results can be utilized to develop comprehensive guidelines that promote effective management and enhance professionalism among university employees.